PENAWARAN DAN PERMINTAAN KOMODITAS KACANGKACANGAN DAN UMBI-UMBIAN DI INDONESIA - MEWA ARIANI (SOCA: Jurnal Sosial Ekonomi Pertanian, 2005)
The food policy is so strong on rice commodity and less noticing other foodcommodities. The objectives of this paper is to analyze supply and demand of beansand tubers in Indonesia, using secondary data from Center Bureaue of Statistic (CBS).The Results are : 1) economic crisis cause the production of beans and tubers decreasedue to the decreasing of planted area. The import of those commodity increase but theirvolume of export tend to decrease; 2) the economic crisis also induces impact onincreasing soybeans and cassava consumption as a result of substitution from animal tovegetables food and from rice to cassava.; 3) food and feed industries development hasa positive growth that can be seen from the increasing volume and value of outputproduct from beans and tubers; 4) in the next 10 years, demand of soybeans will beincreasing but their production tend to decrease. The demand of cassava is alsoincreasing and the production will be decreasing so it cause negative gap betweendemand and production in 2006. In anticipating the demand of beans and tubers,especially for soybeans and cassava, Indonesian Agency of Agricultural Research andDevelopment (AARD) has important role to develop farm technology for increasingproductivity of both commodity. The AARD has a challenge to invent the high varietyof commodity which technically suitable, economically profitable and sociallyacceptable. On the other hand, Indonesian government should arrange tariff policy inimport commodity procedure, especially soybeans, to give protection to the farmer.